PsycEXTRA Dataset 2010
DOI: 10.1037/e597072010-006
|View full text |Cite
|
Sign up to set email alerts
|

Promoting School Connectedness Among Urban Youth of Color: Reducing Risk Factors While Promoting Protective Factors

Abstract: His research program focuses on prevention and resiliency in urban youth, and school-based mental health services. Of primary interest is designing and evaluating culturally relevant and evidence-based psychosocial interventions in youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…School connectedness is linked to improved academic outcomes, and better psychosocial and health status. Adolescents of lower SES, in other studies, have been found to have lower levels of school connectedness, in addition to other social belonging factors that are protective of behavioral and emotional health for adolescents, including community support and parent connectedness . The analyses here indicate the same: there was a strong inverse dose‐response relationship between SES and all 3 dimensions of school connectedness.…”
Section: Discussionsupporting
confidence: 68%
“…School connectedness is linked to improved academic outcomes, and better psychosocial and health status. Adolescents of lower SES, in other studies, have been found to have lower levels of school connectedness, in addition to other social belonging factors that are protective of behavioral and emotional health for adolescents, including community support and parent connectedness . The analyses here indicate the same: there was a strong inverse dose‐response relationship between SES and all 3 dimensions of school connectedness.…”
Section: Discussionsupporting
confidence: 68%
“…Young people rely on community spaces to rest their bodies and engage in points of recovery; dimensions of social connectedness reveal the ways in which this recovery manifests in their lives. Social connectedness is an indicator of well‐being and continues to function as a protective factor for young people (Daly and others, ; World Health Organization, ). Boomerang must continue to be a champion and identify ways to reach beyond the borders of their programme and into schools and families in order to strengthen their capacity to reduce hostility and create more opportunities for young people to develop and grow.…”
Section: Resultsmentioning
confidence: 99%
“…Schools sever the connections young people have with adults and peers in school through suspension and, without accessible and supportive spaces, young people will encounter challenges in promoting recovery and personal and academic growth (Daly and others, ; Losen and Martinez, ; Theriot and Dupper, ). Nelson and Prilleltensky () suggested that recovery occurs when individuals have opportunities to achieve personal goals, experience hope and connect with others during points of disruption in their lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…92 R. A. VIDOUREK AND K. A. KING Interestingly, a large body of research has been devoted to school connectedness in urban schools and with students from lower socioeconomic backgrounds (Battistich & Hom, 1997;Battistich et al, 1995;Becker & Luthar, 2002;Daly, Buchanan, Dasch, Eichen, & Lenhart, 2010). Research indicates that urban students who feel they do not belong at school tend to disengage from school, do not adopt the norms and values of the school, and ultimately, drop out (Walton & Cohen, 2007).…”
Section: Enhancing School Connectednessmentioning
confidence: 95%